Prevalence of low back pain with its associated risk factors among health science students / Nur Fatehah Basri ... [et al.] - Basri, Nur Fatehah; Masuri, Mohammad Ghazali; Danis, Ajau; Isa, Siti Nor Ismalina; Abd Aziz, Nor Azimah; Md Isa, Khairil Anuar (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Low back pain (LBP) has been recorded as a disease with the most numbers to cause the disability and postural condition. However, there are few studies on the prevalence of LBP and its associated risk factors among health science students in Malaysia. Therefore, a cross-sectional study was carried out to investigate the LBP prevalence and its associated factors among health science students enrolled at UiTM Selangor Campus. The LBP was assessed using the Modified Nordic Musculoskeletal Questionnaire which was distributed through an online survey (Google Form). A total of 322 participants took part in this study, of whom 25.5% were currently suffering from LBP. Factors significantly related to LBP were gender (p=0.029), year of study (p=0.036), history of LBP in lifetime (P<0.001), history of LBP for last 12 months (<0.001) and last 7 days (p<0.001), recovery time (p<0.001), type of school bag (p=0.031), work surface (p=0.036) and pressure while studying (p<0.001). However, the impact of performance in daily activities was not significantly associated with LBP. Awareness of the factors associated with LBP should be raised during studies to prevent the occurrence of LBP in health science students.